ANALISIS NIAT BELI ASURANSI JIWA PADA MAHASISWA: APLIKASI THEORY OF PLANNED BEHAVIOR - Pratiwi, Novie Astri; Hartoyo, Hartoyo (Jurnal Ilmu Keluarga dan Konsumen, 2014)
The decision making to buy the life insurance product can be determined by supported attitude for the intention. The purpose of this research was to analyze life insurance purchase intention of college students using the application of the Theory of Planned Behavior (TPB). This research used cross sectional design and involved 250 college students who attended Personal Financial Management Course. Characteristics of college students were measured among three dimensions that were social demography characteristics, value, and financialknowledge. The results indicated that the most of students had high self-respect value score but low security value score. The level of financial knowledge, both subjective and objective measurement of knowledge, attitude toward life insurance product, subjective norms, and perceived behavioral control were considered to be at good level. Further analysis indicates that life insurance purchase intention was significantly correlated with attitudes toward life insurance product (r=0,634; p<0,01), subjective norm (r=0,470; p<0,01), and perceived behavioral control (r=0,508; p<0,01). Life insurance purchase intention is influenced by the value of security and self-respect, subjective financial knowledge, and attitude toward life insurance product.